Dental implant survival in epidermolysis bullosa patients: A systematic review conducted according to PRISMA guidelines and the Cochrane handbook for systematic reviews of interventions - Giuseppe Minervini; Rocco Franco; Maria Maddalena Marrapodi; Antonino Lo Giudice; Marco Cicciù; Vincenzo Ronsivalle (Heliyon, 2024)
Background: Epidermolysis bullosa (EB) is a genetic syndrome afflicting skin and mucous membranes. The manifestation depends on the form: in mild conditions, occasionally, vesicular-bullous lesions of the oral cavity may be present, which heal spontaneously without leaving scars. Patients following joint rupture have scars that limit food intake and restrict quality of life. This study aims to evaluate the possibility of carrying out an implant therapy and the success rate of this therapy. Methods: Until January 3, 2000, PubMed, Web of Science, and Lilacs were searched. Clinical studies were selected that considered implant therapy in patients with epidermolysis bullosa. Articles were therefore selected that addressed oral health and implant survival in patients with epidermolysis, with no differentiation between the various subtypes. A risk of bias assessment was performed through Cochrane. Results: Twenty-one studies were found after the investigation. Only five were chosen to create the current systematic study; 16 articles were skipped over. 10 papers were disregarded because they had been reviewed; 4 were ignored because they contained case studies; and two were omitted because they were not written in English. The results show that implant survival is at around 97%. Conclusions: Patients with epidermolysis bullosa can be treated with implant therapy without the risk of an increased implant failure rate. Indicate the main conclusions or interpretations.